دور تخطيط ورقابة التكلفة التسويقية في زيادة المبيعات: (دراسة ميدانية على عينة من الشركات التجارية بالسودان، 2022) - د. الامين محمود عبد المجيد حسن; محمد السر عطا الله أحمد (White Nile Journal for Studies and Research, 2022)
The research problem was represented in answering the questions: What is the role of planning and controlling marketing costs in increasing sales? The research aimed to determine the relationship between the change in marketing costs and its impact on increasing sales. The research adopted three hypotheses: There is a significant relation between the use of the scientific method to study and analyze the marketing costs elements and the accuracy of their allocation. There is a significant relation between a provision of scientific measures of performance and the scientific planning for the performance of the elements of marketing cost that related to the expected sales, and the existence of a significant relationship between the use of scientific measures to control the effectiveness of marketing costs and achieving Increasing sales. The research used historical, inductive, descriptive and analytical method. The research resulted that: Proving the validity of the hypotheses, supporting the scientific method and the flexibility of measuring marketing costs and using modern costing methods. The accuracy of the link between the cost of advertising campaigns and expected sales contributes to the accuracy of their costing on the market For marketing activities, scientific measures of disclosure contribute to the accuracy of measuring the productivity of long-term marketing costs and achieving the effectiveness of measures of marketing costs during periods of boom and bust, change in consumption pattern, competition, emergence of new products and government intervention in various legislations. Activity units, which increases their effectiveness in increasing sales. The research recommended a number of recommendations, including: The need to pay attention to increasing the awareness of workers about the elements of costs and their behavior and modern methods of controlling them, with an increase in the dose of training on their use through theoretical training and workshops, the need to pay attention to choosing a flexible cost system design commensurate with the nature of the activity and markets of each company that achieves accurate measurement and cost loading with its link to sales to increase its effectiveness.